Spatial control of cAMP signalling in health and disease. - Zaccolo, M (2011)
The cyclic adenosine 3',5'-monophosphate signalling pathway is now recognised to transduce signals in a compartmentalised manner such that individual stimuli only engage a subset of the pathway components that are physically constrained within defined subcellular locales, thus resulting in a precise functional outcome. As we are starting to appreciate the complexity of the spatial organisation and of the temporal regulation of this pathway, it is becoming clear that disruption of local signalling may lead to pathology and that local manipulation of cAMP signals may offer alternative approaches to treat disease.